2019
DOI: 10.1186/s12967-019-2035-8
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cells as a response monitor in stage IV non-small cell lung cancer

Abstract: Background Monitoring circulating tumor cells (CTC) has been shown to be prognostic in most solid malignancies. There is no CTC assay in clinical use for lung cancer therapy monitoring due to inconclusive clinical utility data. Limited data has been published outside of the standard CTC enumerations, regarding clinical significance of phenotypic heterogeneity of CTCs in late stage NSCLC and its ability to correlate with treatment outcomes. Methods In 81 patients with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 50 publications
1
40
0
1
Order By: Relevance
“…In a combined study for metastatic breast and prostate cancer, Coumans et al demonstrated that for initially CTC-positive patients, a decrease of CTC count below the cut-off after 6-8 weeks of therapy is the best indicator of treatment response [38]. The association of therapy response and conversion from positive to negative CTC status was also demonstrated for metastatic non-small cell lung cancer, locally advanced head and neck cancer and gastric cancer [39][40][41]. Lorente et al described a 30% CTC decline 4 weeks after treatment for castration-resistant prostate cancer with initially ≥5 CTCs/7.5 mL as independently associated with OS and a more sensitive biomarker than 50% CTC decline [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a combined study for metastatic breast and prostate cancer, Coumans et al demonstrated that for initially CTC-positive patients, a decrease of CTC count below the cut-off after 6-8 weeks of therapy is the best indicator of treatment response [38]. The association of therapy response and conversion from positive to negative CTC status was also demonstrated for metastatic non-small cell lung cancer, locally advanced head and neck cancer and gastric cancer [39][40][41]. Lorente et al described a 30% CTC decline 4 weeks after treatment for castration-resistant prostate cancer with initially ≥5 CTCs/7.5 mL as independently associated with OS and a more sensitive biomarker than 50% CTC decline [27].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery and development of small molecule TKIs has revolutionized therapy for specific molecular subsets of NSCLC patients [45]. However, the majority of patients will develop resistance to TKIs within a few months/years [45,46]. The resistance is often mediated by a secondary mutation in the target gene or alternative pathways that supervene and bypass the original signaling pathway [47].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells that are detached from the primary tumor site and entered the bloodstream are categorized as CTCs [143]. The implication of CTCs is well established in tumor cell dormancy, as a major cause of metastatic outgrowth, multi drug resistance (MDR) and cancer relapse [144]. These cells are precise representations of primary and metastatic tumors that convey information for the detection, diagnosis (monitoring) and the treatment of cancer [145].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%